Applying methods of the global burden of diseases, injuries, and risk factors study to developmental neurotoxicants: a commentary - David C. Bellinger (BMC, 2018)
Abstract The purpose of this commentary is to consider whether the methods of the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) can provide accurate estimates of the impact of developmental neurotoxicant exposures on population health. The discussion focuses on two concerns. First, GBD implicitly largely endorses a "high risk" or "disease" approach to estimating health loss rather than a "population-based" approach. Exposure to many developmental neurotoxicants is highly prevalent but, for most individuals, it does not affect functional health to such an extent that diagnostic criteria for a disease are met. Nevertheless, the impacts are real and can be substantial when viewed in terms of the aggregate impact on a population. Second, in GBD the disability weights used for the most common sequelae of developmental neurotoxicant exposures, based on judgments provided by general population respondents, are not commensurate with the import that these sequelae have for an individual's lifelong well-being, including their ability to fulfill educational, occupational, and social potential. It would be unfortunate if priorities were set or policy decisions made based on how developmental neurotoxicants compare to other risk factors using the current GBD methods.